Preparation and Characterization of Carbon Foam Derived from Fine Coal and Phenolic Resin - Dodi Irwandi; Zainal Alim Mas’ud; Komar Sutriah; Muhammad Khotib (Indonesian Journal of Chemistry, 2016)
Carbon foam from fine coal and phenolic resin mixture had been prepared by heating in nitrogen atmosphere. The composition of fine coal in a mixture was 30, 35, 40, 45 and 50%. Physical and mechanical characters of carbon foam that were determined from each of these compositions were density, porosity, compressive strength, and oxidation resistance and thermal insulation. Microstructure was observed by scanning electron microscope (SEM). Thermal insulation was tested using an insulation index approach with Styrofoam for comparison. The result showed that the density and compressive strength were proportional to the composition, otherwise, the porosity. Oxidation resistance that was up to 45% composition still showed proportional value. Microstructure observations showed an irregular distribution of pore and uninform diameter. Insulation index of 34 to 50 °C showed almost the same values of all compositions and greater than styrofoam up to 50-150% which mean carbon foam had a better thermal insulation properties than styrofoam.